An adaptive immersed boundary-lattice Boltzmann method for simulating a flapping foil in ground effect. (5th January 2015) - Wu, J.; Qiu, Y.L.; Shu, C.; Zhao, N.; Wang, X.
Highlights: It presents an adaptive immersed boundary-lattice Boltzmann method for simulation of two-dimensional moving boundary problems. A smoothed discrete delta function is utilized to suppress the non-physical force oscillation. The ground effect can improve the lift force and power extraction efficiency of a flapping foil. The ground with a wavy geometry can further increase the improvement. Abstract: An adaptive immersed boundary-lattice Boltzmann method (IB-LBM) for simulating two-dimensional moving boundary problems is presented in this work. On one hand, to accurately and efficiently simulate flow field, our recently developed solution-adaptive LBM (Wu and Shu, 2011) is employed. On the other hand, a smoothed discrete delta function (Yang et al., 2009) is utilized to suppress the non-physical force oscillations produced by IBM when dealing with the moving boundary problems. After simulating some validation cases including flows over a transversely oscillating circular cylinder and insect hovering flight in ground effect, the current method is employed to numerically investigate the ground effect on the performance of a flapping foil. In this study, the ground is represented by a flat or wavy plate. Due to the existence of the ground, the performance of the flapping foil is greatly changed. Higher lift force or power extraction efficiency can be achieved.